2011
DOI: 10.1371/journal.pone.0022921
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish as a Potential Model Organism for Drug Test Against Hepatitis C Virus

Abstract: Screening and evaluating anti- hepatitis C virus (HCV) drugs in vivo is difficult worldwide, mainly because of the lack of suitable small animal models. We investigate whether zebrafish could be a model organism for HCV replication. To achieve NS5B-dependent replication an HCV sub-replicon was designed and created with two vectors, one with HCV ns5b and fluorescent rfp genes, and the other containing HCV's 5′UTR, core, 3′UTR and fluorescent gfp genes. The vectors containing sub-replicons were co-injected into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 36 publications
2
43
0
Order By: Relevance
“…A similar study used fluorescence-labeled HCV subreplicon injected at 1-8 cell-stage zebrafish larvae to study viral tropism in the liver using florescent microscopy. 24 The same study also used conventional reverse transcriptase-PCR and western blot analysis to confirm the effect of antiviral drugs in zebrafish larvae. 24 We found that creating localized wound or injury to anesthetized adult zebrafish kept in an aqueous medium containing a virus supernatant provides an opportunity to facilitate viral infection, which can be visualized or quantified using reporter viruses (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A similar study used fluorescence-labeled HCV subreplicon injected at 1-8 cell-stage zebrafish larvae to study viral tropism in the liver using florescent microscopy. 24 The same study also used conventional reverse transcriptase-PCR and western blot analysis to confirm the effect of antiviral drugs in zebrafish larvae. 24 We found that creating localized wound or injury to anesthetized adult zebrafish kept in an aqueous medium containing a virus supernatant provides an opportunity to facilitate viral infection, which can be visualized or quantified using reporter viruses (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…23 Ding et al, generated a zebrafish larvae model expressing NS5B that amplified the HCV replicon showing expression of HCV core RNA and protein. 24 When ribavirin and oxymatrine, two known anti-HCV drugs were used, the amplification of HCV replicon was inhibited suggesting the use of zebrafish larvae model for screening and evaluation of anti-HCV drugs. 24 In a separate study, it was shown that the HCV core protein with thioacetamide could induce HCV in the zebrafish model in a shorter period of time compared with a mouse model.…”
Section: Viral Tropism In Zebrafish Modelmentioning
confidence: 99%
See 3 more Smart Citations